Christmas wombat - French, Jackie (Boston : Clarion Books, 2012)
"Christmas from a wombat's point of view, including competition for the carrots children have left out for Santa's reindeer, and guess who gets stuck in the chimney?"--Publisher.
Kirkus Starred
School Library Journal
Kirkus Starred, September 2012
School Library Journal, October 2012
0.9
K-3.
Keywords: Wombats -- Juvenile fiction; Christmas -- Fiction; Diaries -- Fiction; Wombats -- Fiction; Christmas -- Fiction; Diaries -- Fiction; JUVENILE FICTION / Animals / Mammals; JUVENILE FICTION / Holidays & Celebrations / Christmas & Advent; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / People & Places / Australia & Oceania; Wombats -- Fiction; Christmas stories; Diary fiction; Picture books for children